Analisis Karakteristik Parkir terhadap Kebutuhan Ruang Parkir di Pasar Central Hamadi Kota Jayapura - Amos Numberi; Petrus Bahtiar; Johni J. Numberi (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2021)
This study aims to determine the capacity needs of the SRP in Hamadi Central Market, Jayapura City. The data required in the form of primary data and secondary data, quantitative and qualitative descriptive analysis approaches to analyze the characteristics of vehicle parking against the needs of SRP in Hamadi Central Market, Jayapura City. The results of the analysis of the parking volume for 92 vehicles and 164 motorcycles, the accumulated parking for 326 vehicles and 301 motorcycles, the parking duration for cars and motorbikes ranged from 1-2 hours, the parking capacity for cars was 39 vehicles / hour and for motorbikes 19 vehicles / hour, 88.3% cars and 90.4% motorbikes, 0.83 car parking turnover rates for cars / parking lots and motorbikes 1.42 motorbikes / parking lots, parking availability 267 vehicles / 9 hours and 119 motorbikes / 9 hours. The result of combining the analysis method, the need for a 46 SRP car and an 88 SRP motorbike means that it exceeds the available SRP. To answer this, an arrangement of the SRP for the car was carried out, so that the SRP for the car was sufficient because the planned SRP was 61 SRP. Meanwhile, to answer the needs of motorbike SRP, which is to move the parking lot into the market / building area, so that the SRP for motorbikes is sufficient because the SRP planned is 108 SRP. The parallel parking pattern is recommended for SRP cars and motorbikes with an angle of 90º.